Pain catastrophizing is associated with high-dose opioids in patients with cancer pain - Simon van Rysewyk; Melanie Lovell; Paul Glare (Academia Medicine)
This study aimed to determine the prevalence of unhelpful pain cognitions, such as catastrophizing and low self-efficacy, and the relationships between pain qualities (severity, interference, distress, and disability) and opioid use in patients with cancer. The study design included the linkage of collected self-report questionnaire responses sourced from the Electronic Persistent Pain Outcomes Collaboration (ePPOC) with medical records in cancer patients referred to a hospital-based pain clinic in Sydney, Australia, from January 2013 to June 2019. Of 267 patients with a history of cancer, 37 (13.8%) had pain attributable to cancer. The average pain intensity was moderate, but severe (≥7/10) in 12 (36%) patients. Unhelpful pain cognitions were common; average scores for pain self-efficacy and catastrophizing were moderate. At referral, most patients were on strong opioids, with many on high doses (>100 mg oral morphine equivalents (OME) per day). Despite higher doses of opioids, pain interference, depression, anxiety, self-efficacy, and catastrophizing scores were worse in patients with severe pain. Pain catastrophizing was significantly higher in the severe group. The correlation between opioid dose with catastrophizing and anxiety indicates that healthcare providers may have not assessed unhelpful pain cognitions, and opioids may have been used by patients to cope with psychological or spiritual distress rather than for analgesia.